Combinatorial Search of Magnetostrictive Materials for Sensors. Issue 9 (September 2014) - Maetani, Takuya; Nakamitsu, Yutaka; Sakurai, Junpei; Nakagawa, Shigeki; Hata, Seiichi
SUMMARY Combinatorial search is one of the useful methods that could search for optimal composition of alloy materials or novel alloy materials. Combinatorial sputtering provides sample group (library) having different compositions in a limited place. Then, the properties of the samples can be scanned in an efficient way. In this research, magnetostrictive material with high magnetostriction, relative permeability, and resistivity was studied. Desired value of magnetostriction is more than 20 × 10−6, relative permeability is more than 4000, and resistivity is more than 100 μΩ·cm. As a result, composition that Cr content is less than 14 at.% fill the desired value of relative permeability, and more than 10 at.% fill the desired value of resistivity. There is possibility to fill the desired value of magnetostriction.